The crisis of Islamic civilization - Allawi, Ali A. (Yale Univ. Press, 2009)
Tearing the fabric -- The break with the past -- The counter-revolt of Islam -- Disenchanting the world -- The reformations of Islam -- Territory and power -- Where next for the Islamic state? -- The rights of man: the duties of man -- Wealth and poverty -- The decline of creativity -- The last crisis